Genome-Wide Analysis of Anthocyanin Biosynthesis Regulatory WD40 Gene FcTTG1 and Related Family in Ficus carica L. - Fan, Zhiyi; Zhai, Yanlei; Wang, Yuan; Zhang, Long; Song, Miaoyu; Flaishman, Moshe A.; Ma, Huiqin (Frontiers in Plant Science, 2022)
WD40 proteins serve as crucial regulators in a broad spectrum of plant developmental and physiological processes, including anthocyanin biosynthesis. However, in fig (Ficus carica L.), neither the WD40 family nor any member involved in anthocyanin biosynthesis has been elucidated. In the present study, 204 WD40 genes were identified from the fig genome and phylogenetically classified into 5 clusters and 12 subfamilies. Bioinformatics analysis prediction localized 109, 69 and 26 FcWD40 proteins to the cytoplasm, nucleus and other cellular compartments, respectively. RNA-seq data mining revealed 127 FcWD40s expressed at FPKM >10 in fig fruit. Most of these genes demonstrated higher expression in the early stages of fruit development. FcWD40-97 was recruited according to three criteria: high expression in fig fruit, predicted nuclear localization, and closest clustering with TTG1s identified in other plants. FcWD40-97, encoding 339 amino acids including 5 WD-repeat motifs, showed 88.01% and 87.94% amino acid sequence similarity to apple and peach TTG1, respectively. The gene is located on fig chromosome 4, and is composed of 1 intron and 2 exons. Promoter analysis revealed multiple light-responsive elements, one salicylic acid-responsive element, three methyl jasmonate-responsive elements, and one MYB-binding site involved in flavonoid biosynthesis gene regulation. FcWD40-97 was in the FPKM >100 expression level group in fig fruit, and higher expression was consistently found in the peel compared to the flesh at the same development stages. Expression level did not change significantly under light deprivation, whereas in leaves and roots, its expression was relatively low. Transient expression verified FcWD40-97’s localization to the nucleus. Yeast two-hybrid (Y2H) and biomolecular fluorescence complementation (BiFC) assays revealed that FcWD40-97 interacts with FcMYB114, FcMYB123, and FcbHLH42 proteins in vitro and in vivo, showing that FcWD40-97 functions as a member of the MYB–bHLH–WD40 (MBW) complex in anthocyanin-biosynthesis regulation in fig. We therefore renamed FcWD40-97 as FcTTG1. Our results provide the first systematic analysis of the FcWD40 family and identification of FcTTG1 in fig pigmentation.